Perancangan Jaringan Fiber To The Home (FTTH) PT. Telkom Indonesia (Persero) Tbk Witel Makassar di Desa Bontomanai Bulukumba - Mahjud, Ichsan; Nirwana, Hafsah; Andhika, Andi; Mimsyad, Muhammad; Litha, Arni; Yuniarti, Yuniarti; Halide, Lidemar (Jurnal Teknologi Elekterika, 2022)
Fibre Optics is a delivery medium to connect network points to multipoint. FTTH is a service provided to customers to meet internet needs in terms of voice, data and video (triple play) services. PT. Telkom has standards for determining network eligibility, namely Power Link Budget and Rise Time Budget. With a case study in Bontomanai Village, Bulukumba, it is possible to simulate the design of the FTTH network to measure BER (Bit Error Rate) for system performance. From the results of network design calculations that the Power Link Budget, one of which is the attenuation from STO to the customer, is 25.65 dB, where this value is still feasible because it is still in the standard range of PT. Telkom is 13 – 28 dB. The Rise Time Budget parameter obtained based on the analysis is 0.262 ns which has not yet crossed the NRZ degradation limit of 0.28 ns. Simulations have been carried out using Optisystem software to measure BER